Translations Of The World’s Literature - Kenan Erzurum (Türk Kütüphaneciliği)
This study investigates the translation of books that have several names like “Translations from World Literature”, “Classics of Ministry of National Education”. Also in this article, there is some information about translation office of Ministry of National Education and printing houses.